2007
DOI: 10.1097/hjh.0b013e328011dc6c
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors in hypertensive patients with coronary artery disease and coexisting renal artery stenosis

Abstract: In conclusion, renal artery stenosis is prevalent in a significant proportion of patients undergoing cardiac catheterization. Renal angiography should be considered particularly in hypertensive patients with multivessel coronary disease coexisting with cardiovascular risk factors, even moderately impaired renal function and increased carotid IMT or vascular disease elsewhere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
3
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 18 publications
7
56
3
1
Order By: Relevance
“…37,38 Owing to ethical concerns, mostly considering the possibility of contrast-induced nephropathy, our study included only hypertensive patients. Table 3 shows that, except for Aqel et al's 1 study, which included a high-risk group and reported an incidence of 28% for RAS in hypertensive patients with suspected CAD, the prevalence of RAS in hypertensive patients varied from 12% in the study of Dizelinska et al 12 to 19.2% in the study of Rihal et al; 10 the prevalence was 11.9% in our study. Studies that did not use hypertension as an inclusion criterion reported RAS incidence up to 15%.…”
Section: Discussioncontrasting
confidence: 38%
See 2 more Smart Citations
“…37,38 Owing to ethical concerns, mostly considering the possibility of contrast-induced nephropathy, our study included only hypertensive patients. Table 3 shows that, except for Aqel et al's 1 study, which included a high-risk group and reported an incidence of 28% for RAS in hypertensive patients with suspected CAD, the prevalence of RAS in hypertensive patients varied from 12% in the study of Dizelinska et al 12 to 19.2% in the study of Rihal et al; 10 the prevalence was 11.9% in our study. Studies that did not use hypertension as an inclusion criterion reported RAS incidence up to 15%.…”
Section: Discussioncontrasting
confidence: 38%
“…Similar differences in groups have been found in other studies. [11][12][13][14][15][16][17][18][19] The higher rate of RAS among patients with a history of CABG in our study and that of Cohen et al 19 reflects a higher prevalence among patients with multi-vessel CAD. This finding may certify that RAS is a manifestation of diffuse atherosclerosis and has a higher prevalence in those with CAD and PAD.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Indeed, RAAS was strongly correlated with cardiovascular markers and RAAS (+) patients frequently developed CVREs as a complication, both here and elsewhere. 6,19,20 RAAS is also closely related to arteriosclerosis of the coronary artery, 21-23 as well as to a significant reduction in cardiac function, 24 which when combined with the reduction in renal function is deemed to make patients prone to heart failure. Indeed, our bilateral RAAS (+) patients were deemed to be especially prone to experience a decline in eGFR, even despite the more aggressive interventions compared to those offered to individuals with unilateral RAAS.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5] Atherosclerotic RAS is a progressive disease leading to renal atrophy over time and chronic kidney disease despite control of HTN. [6][7][8][9][10][11][12][13] Presence and severity of incidental RAS is an independent predictor of mortality in atherosclerotic patients regardless of the mode of treatment of underlying coronary artery disease [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%